Magneto-optical absorption properties of a Weyl semimetal thin film - T. Hoa Le; T. T. Phuong Le; V. Phuc Huynh (Tạp chí Khoa học Đại học Huế: Khoa học Tự nhiên)
In this study, we investigate the magneto-optical absorption properties of a Weyl semimetal thin film by calculating the magneto-optical absorption coefficients (MOACs) for both intra-band and inter-band transitions. The wave function and energy spectrum were determined using the Hamiltonian minimal model in the presence of magnetic and electric fields. The expressions for the MOACs in both x- and z-directions are obtained using the compact density matrix approach. The numerical results demonstrate that the MOACs are significantly influenced by temperature, carrier concentration, and magnetic and electric fields.